Implementation, control and user-feedback of the Int2Bot for the investigation of lower limb body schema integration - Schultje, F.; Wojtusch, J.; Christ, O.; Beckerle, Philipp (IEEE RO-MAN 2014 - 23rd IEEE International Symposium on Robot and Human Interactive Communication: Human-Robot Co-Existence: Adaptive Interfaces and Systems for Daily Life, Therapy, Assistance and Socially Engaging Interactions, 2014)
The integration of prostheses or wearable robotics into the body schema of their users is a fundamental requirement for the acceptance and control of such artificial devices. Duration and progress of integration are primarily influenced by visual, tactile, and proprioceptive perception. This paper describes the Int2Bot, a robot for the assessment of lower limb body schema integration during postural motion. The robot is designed to imitate human squatting movements to investigate the integration of artificial limbs into the body schema. The psychological and technical concepts as well as the mechatronic implementation and control are presented along with interface extensions comprising human knee position sensing and tactile user-feedback. The performance of the robot is examined by experiments excluding and including the human-robot interface and a human user. Those without interface show that the robot itself can perform considerably fast squats with 0.8 Hz, which comes up to maximum human capabilities. The computed torque control achieves good tracking results and fuzzy-based friction compensation further reduces position errors by up to 50%. Yet, results considering the vision-based part of the human-robot interface show that the setup is mainly limited due to delays in motion acquisition with the RGB-D sensor.
CRIS-Team Scopus Importer:2021-09-24